Current status of the adjustable transobturator male system (ATOMSTM) for male stress urinary incontinence - Juliebø-Jones, Patrick; Roth, Ingunn; Tzelves, Lazaros; Hjelle, Karin M.; Moen, Christian Arvei; Esperto, Francesco; Somani, Bhaskar K.; Beisland, Christian (Frontiers in Surgery, 2024)
Male stress urinary incontinence is a debilitating condition, which can occur after prostate surgery. In persistent cases, surgery is indicated and a number of options are available. This includes one of the male slings, Adjustable transobturator male system (ATOMS TM , A.M.I, Austria). There are now an increasing number of studies published. This reviewer provides an overview of the current status of this implant device including technical considerations, surgical outcomes and potential advantages and disadvantages compared to alternatives such as the artificial urinary sphincter.